Shaking Table Tests and Numerical Analysis of a Steel Frame Employing Novel Variable-Coefficient Viscous Dampers - Muhan Liu; Chuying Cao; Zhenyu Zhu; Weizhi Xu; Dongsheng Du; Shuguang Wang; Chuanzhi Sun (Buildings)
Variable-coefficient viscous dampers (VVDs) have a variable annular gap, allowing them to dynamically adjust the damping coefficient at different displacement stages and provide higher damping forces during large displacement phases. This study evaluates the seismic performance of a steel frame equipped with VVDs. A shaking table test was conducted on a two-story, single-span steel frame with the VVDs to assess its seismic response, and the results were compared with those of the same frame equipped with conventional viscous dampers (VD). The experimental results demonstrated that the VVDs significantly reduced the structural dynamic response at various levels of earthquake intensity, consistently outperforming the VDs in terms of the seismic reduction effectiveness. Subsequently, a constitutive model for the VVD element was developed using the open-source finite element software OpenSees3.3.0. The accuracy of the developed element was validated by comparing the finite-element analysis results with mechanical performance tests of the VVD. Based on the developed VVD element, a numerical model of test structure was established in OpenSees for time–history analyses. The results showed good agreement between the numerical simulations and shaking table test data. Finally, a parametric study was conducted on the effects of the ratio <semantics>r</semantics> of the second-order damping coefficient to the first-order damping coefficient and the velocity index α of the VVD on the seismic response of the numerical model of the tested structure. The results indicated that the seismic reduction rate of the tested structure increased with <semantics>r</semantics>, with a maximum improvement of 24%, while it decreased with increasing α, with a maximum reduction of 27%.